Membebaskan Ilmu Sosial dari Keterperangkapan Ganda - Somantri, Gumilar Rusliwa (Jurnal Ilmu Sosial dan Ilmu Politik, 2005)
Social Science in Indonesia facing the challenge to he more authonomous. The science and scientist have to involve themself in a productive dialog with the Western tradition and at the same time, play a significant role in answering the problems related to the ongoing social change. It seems, it is a must for social science to escape itself from the multiple traps of assumption, theory, methodology and orientation, in order to answer successfully the challenge of dynamics of humanity and civilization.